Reconstruction of msadh gene - Ho, Carl Miew (Universiti Malaysia Sarawak (UNIMAS), 2011)
Alcohol dehydrogenase (Adh) genes are highly characterized in alcoholic pathway which normally occurs in most of plants. These genes are activated when under anaerobic stresses by producing measurable level of alcohol dehydrogenase enzyme which is capable in converting acetaldehyde into relatively low toxicity compound, ethanol. This vital response of plants has been proved in enhancing the potential for survival under hypoxic conditions with a low production of A TP and regeneration of NAD+· The objective of this study was to identify and verify the presence of AdhipET inserts within plasmid which is isolated from Metroxylon sagu via Restriction endonuclease and Polymerase Chain Reaction. In addition, reconstruction of the msAdh plasmid was carried out due to the frame shift of single nucleotide.